Enthalpic incompatibility between two steric stabilizer blocks provides control over the vesicle size distribution during polymerization-induced self-assembly in aqueous media - Beattie, Deborah L. (Royal Society of Chemistry, 2020)

(untitled) (Chem Sci)
Over the past two decades, block copolymer vesicles have been widely used by many research groups to encapsulate small molecule drugs, genetic material, nanoparticles or enzymes. They have also been used to design examples of autonomous self-propelled nanoparticles. Traditionally, such vesicles are prepared via post-polymerization processing using a water-miscible co-solvent such as DMF or THF. However, such protocols are invariably conducted in dilute solution, which is a significant disadvantage. In addition, the vesicle size distribution is often quite broad, whereas aqueous dispersions of relatively small vesicles with narrow size distributions are highly desirable for potential biomedical applications. Alternatively, concentrated dispersions of block copolymer vesicles can be directly prepared via polymerization-induced self-assembly (PISA). Moreover, using a binary mixture of a relatively long and a relatively short steric stabilizer block enables the convenient PISA synthesis of relatively small vesicles with reasonably narrow size distributions in alcoholic media (C. Gonzato et al., JACS, 2014, 136, 11100–11106). Unfortunately, this approach has not yet been demonstrated for aqueous media, which would be much more attractive for commercial applications. Herein we show that this important technical objective can be achieved by judicious use of two chemically distinct, enthalpically incompatible steric stabilizer blocks, which ensures the desired microphase separation across the vesicle membrane. This leads to the formation of well-defined vesicles of around 200 nm diameter (size polydispersity = 13–16%) in aqueous media at 10% w/w solids as judged by transmission electron microscopy, dynamic light scattering and small-angle X-ray scattering.